Pengaruh Pendidikan Ekonomi Digital terhadap Penyerapan Tenaga Kerja - Cindi Anjuani Gultom; David Silitonga; Octavianty Sihombing; Siska Lumban Batu; Sovia Elphani Simarmata; Mica Siar Meiriza (Universitas 45 Surabaya, 2025)
This study aims to determine the effect of digital economic education on employment. As well as to provide knowledge to readers how much influence digital economic education has on employment, especially in economic education students at Medan State University. The research method used is the quantitative approach method. The population in this study were 49 students of the Economic Education study program at Medan State University. The research instrument used is a questionnaire in the form of google from which is distributed via whatsapp groups of economic education students. The data that has been collected is analyzed using simple correlation analysis techniques. The results of this study indicate that digital economic education has a positive and significant effect on employment.